EVALUASI PENGELOLAAN OBAT PADA EMERGENCY KIT DI RUANGAN RAWAT INAP PADA RUMAH SAKIT BINA SEHAT JEMBER - Kukuh Judy Handojo, Vieca Fauziah , Dewi Rashati (AKADEMI FARMASI JEMBER, 2019)
Emergency kit management is an important thing to get pay attention because it might be prompt the sentinel event and undesirable effect. Emergency preparations are the medicines that categorized as life saving or life threatening medicines including the medical devices that support emergency condition. The purpose of this study was to determine the percentage of medicine management of emergency kit. The type of research used is descriptive qualitative research and cross sectional (point time approach). The research was conducted in June 2018 at Bina Sehat Hospital Jember. Population and sample in this research is all the medicine management of emergency kit which exist in inpatient room of Bina Sehat Hospital Jember. The sampling technique used is total sampling technique, where all the population used as sample. Research tool of data collection used in this research is using check list. The result of medicine management of emergency kit percentage in inpatient room of Bina Sehat Hospitel Jember regarding the storage management of medicines in emergency kit as much as 59% according to SOP. Distribution of medicines in emergency kit as much as 86,7% according to service guidelines. Replacement medicines that has been used as much as 83% according to SOP. Replacement medicines that damaged or expired as much as 66,6% according to SOP. Monitoring of medicines in emergency kit as much as 84% according to SOP.Keywords : Evaluation, Management, Emergency kit, Pharmacy Installation, Emergency medicine